2008
DOI: 10.1111/j.1469-0691.2007.01934.x
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired methicillin-resistant Staphylococcus aureus infections: an emerging threat in Spain

Abstract: Community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) has not been recognised previously as a cause of MRSA infections in Spain. Nineteen patients carrying Panton-Valentine leukocidin (PVL)-positive MRSA were identified in a Barcelona hospital, of whom 15 were immigrants, mostly from South America. Twelve developed skin and soft-tissue infections. The associated isolates carried the PVL gene and staphylococcal chromosomal cassette (SCC)mecIV. A dominant clone belonging to sequence type (ST)8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
8

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 22 publications
3
36
0
8
Order By: Relevance
“…Between January 1998 and June 2003, the annual average percentage of S. aureus isolates that were MRSA increased further to 51.6% of ICU and 42% of inpatient non-ICU S. aureus isolates (240). Similar persistently high or increasing rates of MRSA among S. aureus isolates have also been observed for health care settings in many other regions of the world (11,32,181,253,278,291,394,539,579,692,899).…”
Section: Emergence and History Of Mrsasupporting
confidence: 63%
“…Between January 1998 and June 2003, the annual average percentage of S. aureus isolates that were MRSA increased further to 51.6% of ICU and 42% of inpatient non-ICU S. aureus isolates (240). Similar persistently high or increasing rates of MRSA among S. aureus isolates have also been observed for health care settings in many other regions of the world (11,32,181,253,278,291,394,539,579,692,899).…”
Section: Emergence and History Of Mrsasupporting
confidence: 63%
“…This specific epidemiology is worrying because of the enhanced virulence and transmissibility of this clone and the rapid spread that has recently occurred in the United States (24,27,31). Second, transatlantic import of USA300 strains has been previously described (21,33) and seems to be the way they were acquired in the case series previously published in Spain (4,5,22). Our results demonstrated that domestic spread now seems to be the most prominent dissemination route in the Bilbao area.…”
mentioning
confidence: 51%
“…Por tanto, los movimientos migratorios están contribuyendo a modificar la naturaleza y frecuencia de los tipos/genotipos de los patógenos circulantes en España, al menos para los casos del VIH y M. tuberculosis, lo que puede llevar aparejados cambios en las pautas de tratamiento 17 , en su patogenicidad 4 y en la frecuencia de mutaciones de resistencia 28 .…”
Section: Discussionunclassified
“…Para los restantes patógenos considerados en los trabajos analizados, los objetivos más frecuentes en estudio fueron el genotipado, en el caso de los virus de la hepatitis B [25][26][27] , de la hepatitis E 7 y el HTLV 10 y de Phleboteomus sergenti 14 y el estudio de mutaciones de resistencia, en S. aureus 28,29 . El único estudio con el virus de la rubeola 30 se centró en el análisis de un brote y el correspondiente a las filariasis 15 en el desarrollo de un diagnóstico molecular para el nematodo causante de la infección.…”
Section: Figura 2 Distribución De Los Trabajos Publicados Sobre Epideunclassified